Dreaming of a Heart Lake Christmas - Robinson, Sarah (Heart Lake, 2022)
"To raise enough money to start her own business, Nola Bennett needs to sell "The Castle," her beloved grandmother's historic house and get back home to the city. But Heart Lake's most eligible bachelor is insisting she hang on to the property. He may be one of the hottest, grumpiest men she's ever seen, but Nola has no time to pine over her high school crush. All woodworker Tanner Dean wants for Christmas is some peace and quiet, but that's not going to happen with infuriating, irresistible Nola Bennett back in town. How can he persuade her to keep The Castle out of the hands of greedy developers when sizzling attraction flares every time they're together? And the more time he spends with Nola, the harder it becomes to picture a future without her--unless he can convince her, once and for all, that Heart Lake is exactly where she belongs." --